The Role of Decision Support System in Improving Efficiency and Quality of Hospital Services in Developing Countries: A Literature Review - Afriyana Amelia Nuryadin; Andi Indahwaty Sidin; Lalu Muhammad Saleh; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The development of information technology, especially the Decision Support System (DSS), has had a significant impact on improving the quality of health services in hospitals. DSS supports data-based decision making, allowing for more accurate diagnosis and efficiency in managing hospital resources. However, the implementation of DSS in developing countries faces technical challenges and resistance from medical personnel.This study aims to explore the benefits and constraints of DSS implementation in a hospital context, with a focus on developing countries. Methods :The method used is a systematic literature review , where related articles are collected from the PubMed, Google Scholar, and ScienceDirect databases. Articles are selected based on relevant inclusion criteria and then analyzed to identify thematic patterns and factors that influence the success of DSS implementation . Results : research shows that DSS can improve operational efficiency and accuracy in clinical decision making. However, challenges include limited technology infrastructure, high training requirements, and high implementation costs. More intensive collaboration between technology developers and end users is needed to maximize DSS acceptance and overcome existing resistance . Conclusion :DSS has great potential in improving the quality of hospital services in developing countries. However, infrastructure readiness and intensive training support factors need to be considered to ensure successful and sustainable implementation .